Analisis Sikap Profesional Auditor dalam Meningkatkan Kinerja Auditor dan Kualitas Audit - Devi Pertiwi Ananda Putri; Ilvia Azhari; Jaya Frediyanto; Dwi Suhartini (Jurnal Akuntan Publik, 2023)
The aim of the research is to analyze factors that can improve auditor performance and audit quality, one of which is in terms of the auditor's professional attitude. This research uses the System Literature Review method using data sources from Google Scholar indexed by Sinta 1-5, Garuda, or Index Copernicus and reputable international journals indexed by Scopus over a period of 6 years from 2018-2023. Article searches were carried out using the keywords professional attitude, auditor performance, and audit quality with the subject KAP in East Java. The research results show that a professional attitude is very important for an auditor to carry out their profession. This is because the auditor's high professional attitude can determine the auditor's performance and better audit quality. Auditor performance is reflected in the auditor's ability to meet predetermined deadlines, while audit quality is reflected in the independence of providing audit opinions. The practical implications of this research mean that an auditor is obliged to uphold the code of ethics of the public accounting profession, such as integrity, objectivity, prudence, professionalism and confidentiality.